Den of iniquity [compact disc, unabridged] - Jance, Judith A. (Jance, Judith A. J. P. Beaumont mysteries., 2024)
Former Seattle homicide cop J. P. Beaumont faces trouble as both his personal and professional lives are thrown into turmoil. Besides Beau's family troubles, a friend asks for his help in what is supposedly an accidental death, and Beau agrees to unofficially reopen the case. It will take everything Beau has to track down a dangerous vigilante killer.